Morphological and molecular characterization of three new Parastenocarididae (Copepoda: Harpacticoida) from caves in Southern Italy - Bruno, Maria Cristina; Cottarelli, Vezio; Marrone, Federico; Grasso, Rosario; Stefani, Erika; Vecchioni, Luca; Spena, Maria Teresa (European Journal of Taxonomy, 2020)
We describe three new parastenocaridid: Cottarellicaris sanctiangeli Bruno & Cottarelli sp. nov., Stammericaris vincentimariae Bruno & Cottarelli sp. nov. and Proserpinicars specincola Bruno & Cottarelli sp. nov., collected in the pools of five different caves located in Calabria (Southern Italy). We conducted a phylogenetic analysis based on the mitochondrial COI and ribosomal 18S sequences of C. sanctiangeli sp. nov. and S. vincentimariae sp. nov., and of four more species of Stammericaris and one Proserpinicaris available from literature. Based on the molecular study, the specimens of C. sanctiangeli sp. nov. are clearly separated from the species belonging to the closely-related genus Stammericaris. The morphological and molecular data indicate that the genera belonging to the two subfamilies Parastenocaridinae and Fontinalicaridinae form two monophyletic and distinct clades, thus supporting their status. We also provide insights on the genus Proserpinicaris based on morphological data only; in particular, the most important synapomorphic character of the genus, i.e., the taxonomic value of the hyaline structure inserted on the anterior surface of the male leg 4 basis, is discussed based on the development of the P4 endopod, as observed in the last copepodid stage of some species of this genus. Finally, we widen the biogeographic and ecological knowledge of the three genera.